Virus-like particles containing a prefusion-stabilized F protein induce a balanced immune response and confer protection against respiratory syncytial virus infection in mice - Luo, Jin; Qin, Huan; Lei, Lei; Lou, Wange; Li, Ruitong; Pan, Zishu (Frontiers in Immunology, 2022)
Respiratory syncytial virus (RSV) is a serious respiratory pathogen in infants and young children worldwide. Currently, no licensed RSV vaccines are available. In this study, we explored stable prefusion conformation virus-like particles (Pre-F VLPs) as RSV vaccine candidates. RSV fusion (F) protein mutants were constructed to form stabilized Pre-F or postfusion (Post-F) configurations. VLPs containing Pre-F or Post-F protein were generated using a recombinant baculovirus (rBV)-insect cell expression system. The assembly and immunological properties of Pre-F or Post-F VLPs were investigated. Pre-F and Post-F VLPs contained antigenic sites Ø and I of pre- and postfusion conformations, respectively. Compared with Post-F VLPs, immunization with Pre-F VLPs elicited upregulation of IFN-γ, IL-2 and IL-10 and downregulation of IL-4 and IL-5 cytokine production in mice. A high percentage of CD25+ Foxp3+ cells or a low percentage of IL-17A-producing cells among CD4+ T cells was observed in the lungs of mice vaccinated with Pre-F VLPs. Importantly, immunization with Pre-F VLPs induced a high level of RSV neutralizing antibody and a balanced immune response, which protected mice against RSV infection without evidence of immunopathology. Our results suggested that Pre-F VLPs generated from rBV-insect cells represent promising RSV vaccine candidates.